A puzzling migratory detour : are fueling conditions in Alaska driving the movement of juvenile sharp-tailed sandpipers? - A Lindstrom; R Gill Jr.; S Jamieson; B McCaffery; L Wennerberg; M Wikelski; Marcel Klaassen (2011)
Making a detour can be advantageous to a migrating bird if fuel-deposition rates at stopover sites along the detour are considerably higher than at stopover sites along a more direct route. One example of an extensive migratory detour is that of the Sharp-tailed Sandpiper ( Calidris acuminata ), of which large numbers of juveniles are found during fall migration in western Alaska. These birds take a detour of 1500-3400 km from the most direct route between their natal range in northeastern Siberia and nonbreeding areas in Australia. We studied the autumnal fueling rates and fuel loads of 357 Sharp-tailed Sandpipers captured in western Alaska. In early September the birds increased in mass at a rate of only 0.5% of lean body mass day -1 . Later in September, the rate of mass increase was about 6% of lean body mass day -1 , among the highest values found among similar-sized shorebirds around the world. Some individuals more than doubled their body mass because of fuel deposition, allowing nonstop flight of between 7100 and 9800 km, presumably including a trans-oceanic flight to the southern hemisphere. Our observations indicated that predator attacks were rare in our study area, adding another potential benefit of the detour. We conclude that the most likely reason for the Alaskan detour is that it allows juvenile Sharp-tailed Sandpipers to put on large fuel stores at exceptionally high rates.